Innovation and employment - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 2011)
Is employment higher in an economy that has a higher rate of innovation? In Hoon and Phelps (1997), we study this question in the small open, and closed, economy under the assumption that the rate of technological progress is exogenous to the economic system.In this paper, we reexamine this question in the context of a model with endogenous product innovation (and thus endogenous technological progress) and endogenous labor supply first in a small open economy taking the world interest rate as given and then ina closed economy that determines the whole term structure of the interest rate. In our present model, creating a given flow of new ideas per unit time directly generates labor demand. Indirectly, as later innovations can benefit from a larger stock of ideas (“the standing on the shoulders of giant” effect), thus requiring less R&D labor input to create a new idea, an economy that has been growing more rapidly in the past demands less labor input now to create a given flow of new ideas. Another source of labor demand in our model economy comes from the production of a variety of intermediate inputs whose product designs have already been discovered through past R&D activity. We find that in both the small open economy and the closed economy, a policy shock that leads to a higher rate of innovation also increases aggregate labor demand. When a shock leads the model economy to transit to a higher steady-growth path, the transition path is characterized unambiguously by rising stock market capitalization (taken as a ratio to GDP) in the closed economy. In the small open economy, there is the possibility that higher growth is accompanied by declining stock market capitalization (taken as a ratio to GDP) as GDP races ahead of the stock market on the transition path. In both cases employment is unambiguously rising with the possibility of overshooting in the small open economy. In terms of labor supply, the transition to a higher steady-growth path leads agents to plan a rising path of employment until they reach the steady state where employment stays constant at a permanently higher level absent another shock. What induces agents to keep postponing their leisure along such a transition path is the falling consumption-growth-adjusted real rate of interest and accelerating wage increases. The prospect of a permanently higher debt-to-GDP ratio in the future requiring a higher payroll tax rate to ensure fiscal solvency leads to a transient period of slower innovation,declining or rising stock market capitalization (taken as a ratio to GDP), and reduced employment in the small open economy. In the closed economy, the same shock has permanent effects as the economy settles on a lower steady-growth path with reduced employment and lower stock market capitalization (taken as a ratio to GDP).